2018
DOI: 10.1038/eye.2017.272
|View full text |Cite
|
Sign up to set email alerts
|

Optimising tear replacement rheology in canine keratoconjunctivitis sicca

Abstract: Dry eye is a substantial problem in a large number of human and canine patients. Numerous laboratory models for tear deficiency exist using genetically predisposed rodent models, animals treated with topical anti-muscarinics, or those kept in environments with increased air flow to produce the ocular surface changes seen in human patients. Canine keratoconjunctivitis sicca, seen in many thousands of dogs kept as companion animals, can provide a valuable spontaneous model for testing tear replacement medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Testing a cross-linked HA product in this model, they observed its non-Newtonian rheology as normal tear film and its tear-like properties. 45 Fallacara et al demonstrated the re-epithelization properties of 2 different concentrations containing a new urea-crosslinked HA: 0.02% (w/v) and 0.4% (w/v). 46 The study was conducted on both two-dimensional human corneal cells and 3D reconstructed tissues of human corneal epithelium.…”
Section: Fig 2 Example Of a Crosslinked Ha Moleculementioning
confidence: 99%
“…Testing a cross-linked HA product in this model, they observed its non-Newtonian rheology as normal tear film and its tear-like properties. 45 Fallacara et al demonstrated the re-epithelization properties of 2 different concentrations containing a new urea-crosslinked HA: 0.02% (w/v) and 0.4% (w/v). 46 The study was conducted on both two-dimensional human corneal cells and 3D reconstructed tissues of human corneal epithelium.…”
Section: Fig 2 Example Of a Crosslinked Ha Moleculementioning
confidence: 99%